2009
DOI: 10.1007/s00404-008-0921-z
|View full text |Cite
|
Sign up to set email alerts
|

The influence of peritoneal endometriotic lesions on the generation of endometriosis-related pain and pain reduction after surgical excision

Abstract: The present study suggests that the surgical excision of endometriotic lesions -- including peritoneal implants -- is an effective treatment of endometriosis-associated pelvic pain and/or dysmenorrhoea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…3 In addition, a significant pain reduction in women with endometriosis after excision of endometriotic lesions is described. 14 In contrast, some groups propose that the presence of nerve fibers in the endometrium is a pain mediatordependent mechanism, independent from the manifestation of endometriosis, as nerve fibers were seen in patients with painful disorders like fibroids and salpingitis. [15][16][17] Because of this discrepancy, more studies in this area should be done urgently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 In addition, a significant pain reduction in women with endometriosis after excision of endometriotic lesions is described. 14 In contrast, some groups propose that the presence of nerve fibers in the endometrium is a pain mediatordependent mechanism, independent from the manifestation of endometriosis, as nerve fibers were seen in patients with painful disorders like fibroids and salpingitis. [15][16][17] Because of this discrepancy, more studies in this area should be done urgently.…”
Section: Discussionmentioning
confidence: 99%
“…3 In addition, a significant pain reduction in women with endometriosis after excision of endometriotic lesions is described. 14…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that re-operations rates are lower after hysterectomy than after operative laparoscopy [83], probably because uterus contain a great number of neural elements that can contribute to arising and exacerbation of CPP. Moreover, treatment of DIE lesions seems to have more effectiveness in long-term pain relief [84] respect to treatment of endometriomas and superficial peritoneal endometriosis [42, 48], although Kaiser et al [85] evidenced that peritoneal endometriotic lesions could worse the pain after the first step surgery and, for this reason, suggest to pay particular attention in their excision. Surprisingly, Sutton et al [86] showed that CPP return sooner after surgery in patients with endometriosis at minimal and mild stages.…”
Section: Surgical Therapymentioning
confidence: 99%
“…Severe endometriosis is treated surgically, with the aim of removing as many lesions as possible [1]. However, postoperative symptomatic recurrences are frequent and repeat surgery is performed in more than 50% of all patients [2].…”
Section: Introductionmentioning
confidence: 99%